Exploring the crystallization landscape of cadmium bis(N-hydroxyethyl, N-isopropyldithiocarbamate), Cd[S2CN(iPr)CH2CH2OH]2 - Tan, Yee Seng *; Siti Nadiah Abdul Halim,; Tiekink, Edward R. T. * (De Gruyter, 2016)
Crystallization of Cd[S2CN(iPr)CH2CH2OH]2 from ethanol yields the coordination polymer [{Cd[S2CN(iPr) CH2CH2OH]2}·EtOH]∞ (1) within 3 h. When the solution is allowed to stand for another hour, the needles begin to dissolve and prisms emerge of the supramolecular isomer (SI), binuclear {Cd[S2CN(iPr)CH2CH2OH]2}2·2EtOH (2). These have been fully characterized spectroscopically and by X-ray crystallography. Polymeric 1 has 2-fold symmetry and features dithiocarbamate ligands coordinating two octahedral Cd atoms in a μ2κ2-tridentate mode. Binuclear 2 is centrosymmetric with two ligands being μ2κ2-tridentate as for 1 but the other two being κ2-chelating leading to square pyramidal geometries. The conversion of the kinetic crystallization product, 1, to thermodynamic 2 is irreversible but transformations mediated by recrystallization (ethanol and acetonitrile) to related literature SI species, namely coordination polymer [{Cd[S2CN(iPr) CH2CH2OH]2}3·MeCN]∞ and binuclear {Cd[S2CN(iPr)CH2CH 2 OH]2}2·2H2O·2MeCN, are demonstrated, some of which are reversible. Three other crystallization outcomes are described whereby crystal structures were obtained for the 1:2 co-crystal {Cd[S2CN(iPr)CH2CH2OH]2}2:2[3-(propan- 2-yl)-1,3-oxazolidine-2-thione] (3), the salt co-crystal [iPr NH2(CH2CH2OH)]4[SO4]2{Cd[S2CN(iPr)CH2CH2OH]2}2 (4) and the salt [iPrNH2(CH2CH2OH)]{Cd[S2CN(iPr)CH2CH2OH]3} (5). These arise as a result of decomposition/oxidation of the dithiocarbamate ligands. In each of 3 and 4 the binuclear {Cd[S2CN(iPr)CH2CH2OH]2}2 SI, as in 2, is observed strongly suggesting a thermodynamic preference for this form.